2020
DOI: 10.21278/tof.43406
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Cavitating Pulsating Water Jet Used for Removing Contaminants from Metal Surfaces

Abstract: The paper presents an environmentally friendly method for cleaning metal surfaces from contaminants. In this method, the contaminants are removed from surfaces by a cavitating pulsating water jet generated in the nozzle and directed at the surface. The cavitation-generating effectiveness of three various design nozzles was investigated numerically using the SolidWorks 2015 Flow Simulation software. The volume fraction of the vapour generated in the flow inside the nozzles was determined. Selected nozzle was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Single cavitation generating nozzle directed to the surface being cleaned would also be suitable for surface cleaning, but previous research [20] showed that traces of water remain on the cleaned surface, which reduce the efficiency of the proposed method. Therefore, there was a need to design a system (head) with water removal system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single cavitation generating nozzle directed to the surface being cleaned would also be suitable for surface cleaning, but previous research [20] showed that traces of water remain on the cleaned surface, which reduce the efficiency of the proposed method. Therefore, there was a need to design a system (head) with water removal system.…”
Section: Methodsmentioning
confidence: 99%
“…Head consists of three cavitation generating nozzles (atomizers) NECBD [15,20,21] arranged at 120°angle with respect to each other (Figs. 2 and 3, view I).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hua et al [12] developed a new hydroblasting cleanup system that can be loaded onto underwater cleaning robots and can effectively interrupt the growth of marine biofouling. Ralys et al [13] designed a cavitation-generating head with a water removal system and built the prototype, avoiding the possibility that water left on the cleaned surface would decrease the effectiveness of the cavitation jet. It was preliminarily demonstrated that the method of ultrasonic-enhanced submerged cavitation jets for cleaning marine biofouling is practical by Zhong et al [14] when they suggested a new ultrasonic-enhanced submerged cavitation jet ship fouling cleaning technique.…”
Section: Introductionmentioning
confidence: 99%